Nano- and Micro-Patterned S-, H-, and X-PDMS for Cell-Based Applications: Comparison of Wettability, Roughness, and Cell-Derived Parameters - Scharin-Mehlmann, Marina; Häring, Aaron; Rommel, Mathias; Dirnecker, Tobias; Friedrich, Oliver; Frey, Lothar; Gilbert, Daniel F. (Frontiers in Bioengineering and Biotechnology, 2018)
Polydimethylsiloxane (PDMS) is a promising biomaterial for generating artificial extracellular matrix like patterned topographies, yet its hydrophobic nature limits its applicability to cell-based approaches. Although plasma treatment can enhance the wettability of PDMS, the surface is known to recover its hydrophobicity within a few hours after exposure to air. To investigate the capability of a novel PDMS-type (X-PDMS) for in vitro based assessment of physiological cell properties, we designed and fabricated plane as well as nano- and micrometer-scaled pillar-patterned growth substrates using the elastomer types S-, H- and X-PDMS, which were fabricated from commercially available components. Most importantly, we compared X-PDMS based growth substrates which have not yet been investigated in this context with H- as well as well-known S-PDMS based substrates. Due to its applicability to fabricating nanometer-sized topographic features with high accuracy and pattern fidelity, this material may be of high relevance for specific biomedical applications. To assess their applicability to cell-based approaches, we characterized the generated surfaces using water contact angle measurement and atomic force microscopy as indicators of wettability and roughness, respectively. We further assessed cell number, cell area and cellular elongation as indirect measures of cellular viability and adhesion by image cytometry and phenotypic profiling, respectively, using Calcein and Hoechst 33342 stained human foreskin fibroblasts as a model system. We show for the first time that different PDMS types are differently sensitive to plasma treatment. We further demonstrate that surface hydrophobicity changes along with changing height of the pillar-structures. Our data indicate that plane and structured X-PDMS shows cytocompatibility and adhesive properties comparable to the previously described elastomer types S- and H-PDMS. We conclude that nanometer-sized structuring of X-PDMS may serve as a powerful method for altering surface properties towards production of biomedical devices for cell-based applications.